New Measures for Performance Evaluation - Cherny, Alexander; Madan, Dilip (Review of Financial Studies, 2009)
[This paper characterizes performance measures satisfying a set of proposed axioms. We develop four new measures consistent with the axioms and show that they improve on the economic properties of the Sharpe Ratio and the Gain-Loss Ratio. In our treatment, the performance measures, or the indexes of acceptability, are linked to positive expectations resulting from a stressed sampling of the cash-flow distribution. Theoretically, it is shown that the level of acceptability varies directly with the amount of stress tolerated. In an empirical application, the performance measures are applied to cash flows generated by writing options on the SPX and the FTSE. This exercise reveals that acceptability levels are U-shaped in the strike direction.]